2012
DOI: 10.1007/s12263-012-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed hepcidin expression correlates with hypotransferrinemia in copper-deficient rat pups but not dams

Abstract: Copper deficiency leads to anemia but the mechanism is unknown. Copper deficiency also leads to hypoferremia, which may limit erythropoiesis. The hypoferremia may be due to limited function of multicopper oxidases (MCO) hephaestin in enterocytes or GPIceruloplasmin in macrophages of liver and spleen whose function as a ferroxidase is thought essential for iron transfer out of cells. Iron release may also be limited by ferroportin (Fpn), the iron efflux transporter. Fpn may be lower following copper deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These results are consistent with published studies in which copper deficiency led to a decrement in TfR1 protein in the liver [73, 89]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with published studies in which copper deficiency led to a decrement in TfR1 protein in the liver [73, 89]. …”
Section: Discussionsupporting
confidence: 93%
“…Different experimental models have reported some contrasting results such as animals fed a copper-deficient diet showed an increment of Fpn1 protein when whole liver was analysed. This apparent discrepancy could be due to a different response to the same stimuli between the different cells present in this organ, e.g., Kupffer cells and hepatocytes [14, 72, 73]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, one recent study showed that copper treatment induced hepcidin expression in hepatoma cells via transactivation of the Hamp gene promoter by the metal-responsive transcription factor MTF1 (13). In addition, hepcidin expression is diminished in rats (27, 138) and mice (42) in response to copper depletion. Moreover, the biologically active from of the hepcidin peptide (hepcidin-25), binds copper with high affinity (292).…”
Section: Intersection Of Iron and Copper Metabolism In The Livermentioning
confidence: 99%
“…Recent evidence shows that hepcidin expression is decreased by copper restriction in rats (4, 48) and mice (9). Furthermore, it was shown that hepcidin-25, the active form of the peptide, binds copper with high affinity (109).…”
Section: Iron-copper Interactions In Livermentioning
confidence: 99%